Comprehensive gummy smile correction: a case report on combined lip repositioning and crown lengthening - Nurbaiti, Mentari Salma; Murdiastuti, Kwartarini; Karina, Vincensia Maria (Faculty of Dentistry, Universitas Gadjah Mada, 2025)
A gummy smile, or excessive gingival display (EGD), is a clinical condition in which more than 3–4 mm of gingiva is visible during smiling. This condition often raises aesthetic concerns and may negatively affect self-esteem. This report presents the clinical management of a 26-year-old male patient whose gummy smile was attributed to altered passive eruption, compounded by hyperactivity of the upper lip elevator muscles. To address these issues, a combined surgical approach was employed: crown lengthening and lip repositioning. Crown lengthening was performed on teeth 12, 11, and 22 to establish an appropriate tooth–gingiva ratio, while lip repositioning was carried out to limit excessive elevation of the upper lip. Postoperative evaluations revealed a significant correction of the gingival display and improved tooth dimensions. These results highlight the effectiveness of a combined periodontal and soft tissue surgical approach in achieving harmonious and predictable smile aesthetics.